Reduced-order models to analyse coherent structures in turbulent pipe flow - Abreu, Leandra I.; Cavalieri, André V.G.; Schlatter, Philipp; Vinuesa, Ricardo; Henningson, Dan (11th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2019, 2019)
Fully resolved direct numerical simulations, performed with a high-order spectral-element method, are used to study coherent structures in turbulent pipe flow at friction Reynolds numbers Reτ = 180 and 550 (El Khoury et al., 2013). The database was analysed using spectral proper orthogonal decomposition (SPOD) so as to identify dominant coherent structures, most of which are of streaky shape. As a reduced-order model for such structures, the linearised flow response to harmonic forcing was computed, and the analysed singular modes of the resolvent operator were analysed. For turbulent flows, this approach amounts to considering the non-linear terms in the Navier–Stokes system as an unknown forcing, treated convenienty as external. Resolvent analysis then allows an identification of the optimal forcing and most amplified flow response; the latter may be related to observed relevant structures obtained by SPOD, especially if the gain between forcing and response is much larger than what is found for suboptimal forcings or if the non-linear forcing is white noise. Results from SPOD and resolvent analysis were extracted for several combinations of frequencies, streamwise and azimuthal wavenumbers. For both Reynolds numbers, good agreement between SPOD and resolvent modes was observed for parameter combinations where the lift-up mechanism is present: optimal forcing from resolvent analysis represents streamwise vortices and the associated response are streaky structures.
CRIS-Team Scopus Importer:2023-03-21